Children’s Exposure with Technological Gadgets and its Relationship with Gender, Age, and Family Structure: A study on COVID -19 Pandemic - Sadruddin Bahadur Qutoshi; Zahra Jabeen; Sabit Rahim (JECCE, 2023)
Covid-19 pandemic forced roughly 1.5 billion learners around the globe (i.e., from early childhood education to university level) to stay at home. Among them, children have been greatly affected by the lockdown and exposed to a diverse range of technological gadgets. Thus, technological gadgets created an engaging space for children to spend their time at home. In the context of Gilgit-Baltistan (GB), Pakistan, this study examines the children’s exposure with technological gadgets and its relationship with gender, age/grade level, and family structure during Covid-19 pandemic lockdown. Through a survey questionnaire, the data were collected from 150 parents. By using Statistical Package for Social Sciences (SPSS 21.0), the data were analyzed. Both the Descriptive (percentages and frequencies) and Inferential (independent t-test and correlation) statistics were applied. The findings of the study revealed that 18% children at informed parents’ program level (i.e., 0-3years), 40% at ECD level (3-8years) and 42% at upper primary level were expose with technological gadgets. However, boys were found to be more exposed with technological gadgets (i.e., 70.7%) as compared to girls (i.e., 28%) during Covid-19 Pandemic Lockdown period in GB. Findings showed that 38% children were found to be in nuclear families, 55% children were in joint and only 6% were in extended families. Mostly children use mobile and laptop/ computers (39.3%) whereas only 16.7% children use TV in Gilgit. It was also revealed that 58.7% parents supervise while 41.3% parents does not supervise their children while using technological gadgets. However, there was no significant difference between male and female children across age group. The study recommended to carry out a research study in the future to investigate the family structure and use of technological devices by increasing the sample size and research sites to get more insights.